Get rich with Twitter : harness the power of the Twitterverse and reach more customers than ever before - Prince, Dennis L. (New York : McGraw-Hill, 2010)
Experience the "tweet" smell of success!
1. Understanding twitter -- 2. Establishing and tweaking -- 3. Advancing the twitter touch -- 4. Look, listen, and learn: twitter success stories
Includes index
Keywords: Twitter; Business communication; Internet marketing; Online social networks